India-Bangladesh relations : need for new approach - Punam Pandey (2012)
The visit of the Indian prime minister to Bangladesh this week offers opportunity to address emerging challenges in the bilateral relationship arising from climate change. There is a need for fresh approaches by the two neighbours to enhance their fluctuating ties.